2016
DOI: 10.5937/jouproman4-11468
|View full text |Cite
|
Sign up to set email alerts
|

Technology and economic development: Retrospective

Abstract: Abstract:The purpose of this paper is to represent historical link between technological progress and economic development. Furthermore, the reasons are aimed at presenting the stages of development of technological progress and its contribution to economic development, particularly in changing economic and social life. I want to emphasize that many researchers of scientific thought, technological progress has been learned as one of the root causes of cyclical movement of capitalist economy. Others seek to qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…Peningkatan teknologi yang ada pada sutu negara juga memerlukan dorongan dan komitmen pemerintah dalam kegiatan sehari-hari. Selain itu menciptakan iklim menggunakan teknologi dalam setiap kegiatan ekonomi yang disertai dengan proses inovasi sehingga masyarakat menjadi terbiasa juga sangat mempengaruhi tingkat percepatan pertumbuhan ekonomi yang diharapkan mampu meningkatkan kualitas hidup masyarakat (Broughel dan Thiever, 2019;Nikoloski, 2016). Salah satu mem[ budayakan penggunaan teknologi dalam kegiatan ekonomi adalah menggunakan teknologi komunikasi internet dalam setiap kegiatan.…”
Section: Pembahasan Keterkaitan Antara Teknologi Terhadap Pertumbuhanunclassified
“…Peningkatan teknologi yang ada pada sutu negara juga memerlukan dorongan dan komitmen pemerintah dalam kegiatan sehari-hari. Selain itu menciptakan iklim menggunakan teknologi dalam setiap kegiatan ekonomi yang disertai dengan proses inovasi sehingga masyarakat menjadi terbiasa juga sangat mempengaruhi tingkat percepatan pertumbuhan ekonomi yang diharapkan mampu meningkatkan kualitas hidup masyarakat (Broughel dan Thiever, 2019;Nikoloski, 2016). Salah satu mem[ budayakan penggunaan teknologi dalam kegiatan ekonomi adalah menggunakan teknologi komunikasi internet dalam setiap kegiatan.…”
Section: Pembahasan Keterkaitan Antara Teknologi Terhadap Pertumbuhanunclassified
“…However, even before the pandemic, there were digital divides on various fronts. Empirical evidence suggests a substantial technological gap between developed and developing countries (Acheampong, 2020;Nikoloski, 2016). There are also digital divides, both in developing and developed markets (WEF (2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, technological progress has a positive impact on economic growth and human society [1]. Krume Nikoloski (2016) in his study of the relationship between technology and economic development concluded that important factors affecting economic growth are natural resources, human capital, capital information, technological development and socialpolitical conditions [2]. Among these factors, technological development plays an essential role in promoting economic growth and creates continuous opportunities for its further progress.…”
Section: Introductionmentioning
confidence: 99%
“…Today, there is a technological gap between developed and developing countries. Developing countries, those are lack of STI and dependant on developed countries, still have to import modern equipment and technology from countries with more developed technology [2].…”
Section: Introductionmentioning
confidence: 99%